General Principles of Legal Research. Issue 2 (5th October 2020) - Silverman, Marc
Abstract: Having worked for years to distill aspects of the legal research process down to a set of core principles, the author presents a selection, with commentary, for use by instructors in introductory research courses. Examples are provided throughout, drawn from his classroom experience to illustrate the concepts he describes.